A new Kunitz‐type snake toxin family associated with an original mode of interaction with the vasopressin 2 receptor. (28th February 2022) - Droctové, Laura; Ciolek, Justyna; Mendre, Christiane; Chorfa, Amélia; Huerta, Paola; Carvalho, Chrystelle; Gouin, Charlotte; Lancien, Manon; Stanajic‐Petrovic, Goran; Braco, Lorine; Blanchet, Guillaume; Upert, Gregory; et al.
Abstract : Background and Purpose: Venomous animals express numerous Kunitz‐type peptides. The mambaquaretin‐1 (MQ1) peptide identified from the Dendroaspis angusticeps venom is the most selective antagonist of the arginine‐vasopressin V2 receptor (V2R) and the only unique Kunitz‐type peptide active on a GPCR. We aimed to exploit other mamba venoms to enlarge the V2R‐Kunitz peptide family and gain insight into the MQ1 molecular mode of action. Experimental Approach: We used a bio‐guided screening assay to identify novel MQs and placed them phylogenetically. MQs were produced by solid‐phase peptide synthesis and characterized in vitro by binding and functional tests and in vivo by diuresis measurement in rats. Key Results: Eight additional MQs were identified with nanomolar affinities for the V2R, all antagonists. MQs form a new subgroup in the Kunitz family, close to the V2R non‐active dendrotoxins and to two V2R‐active cobra toxins. Sequence comparison between active and non‐active V2R Kunitz peptides highlighted five positions, among which four are involved in V2R interaction and belong to the two large MQ1 loops. We finally determined that eight positions, part of these two loops, interact with the V2R. The variant MQ1‐K39A showed a higher affinity for the hV2R, but not for the rat V2R. Conclusions and Implications: A new function and mode of action is associated with the Kunitz peptides. The number of MQ1 residues involved in V2R binding is large and may explain its absolute selectivity. MQ1‐K39A represents the first step in the improvement of the MQ1 design from a medicinal perspective.